‘Scaling up’ educational change: some musings on misrecognition and doxic challenges - Thomson, Pat (Taylor & Francis, 2014)
Educational policy-makers around the world are strongly committed to the notion of ‘scaling up’. This can mean anything from encouraging more teachers to take up a pedagogical innovation, all the way through to system-wide efforts to implement ‘what works’ across all schools. In this paper, I use Bourdieu’s notions of misrecognition to consider the current orthodoxies of scaling up. I argue that the focus on ‘process’ and ‘implementation problems’: (1) both obscures and legitimates the ways in which the field logics of practice actually work and, (2) produces/reproduces the inequitable distribution of educational benefits (capitals and life opportunities). I suggest that the notion of misrecognition might provide a useful lens through which to examine reform initiatives and explanations of their success/failure.